Rapid Acetabular Chondrolysis following Hemiarthroplasty of the Hip: A Poor Prognostic Sign - Abidemi Adenikinju; James D. Slover; Kenneth A. Egol (Case Reports in Orthopedics)
Both hemiarthroplasty and total hip arthroplasty have been well described as effective methods of management for displaced femoral neck fractures in the elderly. Acetabular erosion is a common long-term complication of hemiarthroplasty. We present a case in which rapid acetabular erosion occurs within weeks of hemiarthroplasty, ultimately leading to an acetabular fracture and need for revision to total hip arthroplasty. Early and rapid acetabular erosion following hip hemiarthroplasty has not been well documented in current literature. It may lead to acetabular fracture and may be secondary to infectious causes. If encountered, an infection workup should be initiated.